Pagan's crusade - Jinks, Catherine (London Collins, 2003)
In twelth-century Jerusalem, orphaned sixteen-year-old Pagan is assigned to work for Lord Roland, a Templar knight, as Saladin's armies close in on the Holy City.
Accelerated Reader AR
Keywords: Crusades -- Third, 1189-1192 -- Juvenile fiction; Crusades -- Third, 1189-1192 -- Fiction; Knights and knighthood -- Fiction; Orphans -- Fiction; Historical fiction